Presence and duration of anti-Toxoplasma gondii immunoglobulin M in infants with congenital toxoplasmosis - Eleonor G. Lago; Anna Paula Oliveira; Ana Lígia Bender (Elsevier, 2014)
Objectives: to investigate the rate of positivity for immunoglobulin M anti-Toxoplasma gondii (Toxo-IgM) in newborns with congenital toxoplasmosis, and the age when these antibodies become negative. Methods: patients with congenital toxoplasmosis who started monitoring in a congenital infection clinic between 1998 and 2009 were included. Inclusion criteria were routine maternal or neonatal serological screening; diagnostic confirmation by persistence of immunoglobulin G anti-Toxoplasma gondii at age ≥ 12 months, and Toxo-IgM screening in the neonatal period. To calculate the frequency of positive Toxo-IgM, cases detected by neonatal screening were excluded. For the study of the age when Toxo-IgM results became negative, patients with negative Toxo-IgM since birth and those in whom it was not possible to identify the month when the negative result was achieved were excluded. Results: among the 28 patients identified through maternal screening, 23 newborns had positive Toxo-IgM (82.1%, 95% CI: 64.7-93.1%). When adding the 37 patients identified by neonatal screening, Toxo-IgM was positive in the first month of life in 60 patients, and it was possible to identify when the result became negative in 51 of them. In 19.6% of patients, these antibodies were already negative at 30 days of life; and in 54.9%, at 90 days. Among the 65 patients included in the study, 40 (61.5%) had some clinical alteration. Conclusions: even with high sensitivity methods, newborns with congenital toxoplasmosis can have negative Toxo-IgM at birth. In those who have these antibodies, the positive period may be quite short. It is important not to interrupt the monitoring of infants with suspected congenital toxoplasmosis simply because they present a negative Toxo-IgM result. Resumo: Objetivos: investigar a taxa de positividade para imunoglobulina M anti-Toxoplasma gondii (Toxo-IgM) em recém-nascidos com toxoplasmose congênita, e a idade de negativação desses anticorpos. Métodos: foram incluídos pacientes com toxoplasmose congênita que iniciaram acompanhamento em uma clínica de infecções congênitas entre 1998 e 2009. Os critérios de inclusão foram toxoplasmose congênita detectada por triagem sorológica materna ou neonatal de rotina, confirmação diagnóstica por persistência de imunoglobulina G anti-Toxoplasma gondii com ≥12 meses e pesquisa de Toxo-IgM no período neonatal. Para o cálculo da frequência de positividade da Toxo-IgM foram excluídos os detectados por triagem neonatal. Para o estudo da época de negativação da Toxo-IgM foram excluídos os pacientes com Toxo-IgM negativa desde o nascimento e aqueles em que não foi possível identificar o mês da negativação. Resultados: entre 28 pacientes detectados por triagem materna, 23 recém-nascidos tiveram Toxo-IgM positiva (82,1%, IC 95%: 64,7-93,1%). Somando-se os 37 pacientes detectados por triagem neonatal, a Toxo-IgM foi positiva no primeiro mês de vida em 60 pacientes e em 51 foi possível identificar a época de negativação. Em 19,6% dos pacientes esses anticorpos já eram negativos aos 30 dias e em 54,9% aos 90 dias. Entre os 65 pacientes incluídos no estudo, 40 (61,5%) apresentaram alguma alteração clínica. Conclusões: mesmo com métodos de alta sensibilidade, recém-nascidos com toxoplasmose congênita podem ter Toxo-IgM negativa ao nascer. Nos que apresentam esses anticorpos, o período de positividade pode ser bastante fugaz. É importante não interromper o monitoramento dos lactentes com suspeita de toxoplasmose congênita por apresentarem Toxo-IgM negativa. Keywords: Congenital toxoplasmosis, Toxoplasma gondii, Immunoglobulin M/ diagnostic use, Serological tests, Neonatal screening, Vertical transmission of infectious disease, Palavras-chave: Toxoplasmose congênita, Toxoplasma gondii, Imunoglobulina M/uso diagnóstico, Testes sorológicos, Triagem neonatal, Transmissão vertical de doença infecciosa